Microbiological Exposure Risk Assessment in Rainwater Harvesting Systems: Implications for Community Health - Sandy Novryanto Sakati; Anwar Mallongi; Erniwati Ibrahim; Budimawan; Sukri Palutturi; Stang; Hasnawati Amqam; Maria Kanan; Herawati (International Journal of Medical Toxicology and Legal Medicine, 2024)
Rainwater harvesting (RWH) systems play a crucial role in addressing water supply challenges, especially in rural areas with limited access to clean water. However, there are significant microbiological contamination risks in RWH, particularly related to the presence of Total Coliform and Escherichia coli (E. coli), which can pose a threat to public health. This study fills the knowledge gap by assessing the levels of microbiological contamination in RWH systems in Bulagi Utara, Banggai Kepulauan Regency. The research uses a quantitative approach with a cross-sectional design, involving water sampling from eight rainwater storage points. The study results indicate that Points V and VIII exhibit high contamination levels exceeding the thresholds set by WHO, indicating potential health risks for communities using untreated rainwater. Regular cleaning and the application of treatment methods such as filtration and disinfection have proven effective in reducing contamination levels. This study provides important implications for improving water quality management in RWH, particularly in rural areas that heavily depend on this water source.